A review of world Diallactiini (Diptera, Cecidomyiidae, Winnertziinae), with the description of six new genera and seventeen new species - Jaschhof, Mathias (Zootaxa, 2016)
Fossil and extant Diallactiini, which are mycophagous Cecidomyiidae (gall midges), are reviewed globally for the first time. Johnsonomyia Felt, 1908 stat. rev. is restored from synonymy with Haplusia Karsch, 1877 (with Chastomera Skuse, 1888 confirmed as a junior synonym) and both genera are re-defined. Haplusia funebris Plakidas, 2007 and Wyattella lobata Yukawa, 1968 are newly combined in Johnsonomyia. Gynapteromyia Mamaev, 1965 is shown to be a species-rich, almost cosmopolitan genus, which absorbs several of the species previously classified in Haplusia or Chastomera. Gynapteromyia brevipalpis (Mamaev, 1964) comb. nov., G. heteroptera (Mamaev & Spungis, 1980) comb. nov., G. hondrui (Mamaev, 1964) comb. nov., G. indica (Grover, 1971) comb. nov., G. longipalpis (Mamaev, 1964) comb. nov., and G. stricta (Fedotova & Sidorenko, 2005) comb. nov. are all new combinations. †Palaeocolpodia eocenica Meunier, 1904 is considered to be a nomen dubium. Prior to the present study, the tribe Diallactiini contained 28 extant species classified in 6 genera. Previously unworked specimens of Diallactiini gathered by the author in the past 15 years were examined and identified as belonging to 57 different species, all unnamed. From that material, the following new taxa are described: Bruneiplusia gen. nov. (from Brunei), B. kaspraki sp. nov., Gynapteromyia costaricensis sp. nov. (Costa Rica), G. furcata sp. nov. (Costa Rica), G. novaezealandiae sp. nov. (New Zealand), G. tasmanica sp. nov. (Australia), G. temburong sp. nov. (Brunei), G. tenuistylata sp. nov. (Brunei), Haplusia afrotropica sp. nov. (South Africa), Japoplusia gen. nov. (Japan), Jap. honshuensis sp. nov., Johnsonomyia scabra sp. nov. (Costa Rica), John. serrata sp. nov. (South Africa), Loboplusia gen. nov. (Costa Rica), L. zurqui sp. nov., Makrostyles gen. nov. (Costa Rica), Makr. terrifica sp. nov., Mikrostyles gen. nov. (Brunei), Mikr. angustilobata sp. nov., Mikr. latolobata sp. nov., Wahabia gen. nov. (Brunei), Wah. mantici sp. nov., and Wyattella japonica sp. nov. (Japan). A key to the genera of Diallactiini based on male characters is presented. Diallactiini are shown to be a remarkably diverse group in terms of adult morphology. The genitalia of some male Diallactiini represent the most strongly modified such structures known in Winnertziinae. Morphological novelties found in Diallactiini, but no other Cecidomyiidae, include the fringed leg setae of Loboplusia and the furcate palpal sensilla in some Gynapteromyia and Mikrostyles. Diallactiini occur in all zoogeographic regions, with the highest generic and specific diversity found in the tropics (although Afrotropical diallactiines are poorly researched). Local diversity is also highest in the tropics, with as many as 29 species (unnamed or named in this paper) of at least 6 genera found at a single site, Zurquí de Moravia, in the cloud forest of Costa Rica. The best-explored fauna of Winnertziinae, including Diallactiini, is certainly that of Europe, but diallactiine biodiversity there is low and most of the nine European species are rarely encountered in the field. Gynapteromyia brevipalpis is reported from Sweden for the first time.